How will you measure your life? - Christensen, Clayton M. 1952-2020 (Harper Business, 2012)
Akin to The Last Lecture in its revelatory perspective following life-altering events, "How Will You Measure Your Life?" presents a set of personal guidelines that have helped the author find meaning and happiness in his life.